Genome-wide identification of TCP transcription factors and functional role of UrTCP4 in regulating terpenoid indole alkaloids biosynthesis in Uncaria rhynchophylla - Xinghui Liu; Yingying Shao; Detian Mu; Yu Zhou; Jialong He; Huan Zhao; Iain W. Wilson; Yao Zhang; Lina Zhu; Deyou Qiu; Qi Tang (Current Plant Biology)
Uncaria rhynchophylla is a widely used Chinese herbal medicine known for its terpenoid indole alkaloids (TIAs), which help in treating hypertension. Teosinte branched 1/cycloidea/proliferating cell factors 1/2 (TCP) TFs have been shown to have a role in the growth and development of plants, but the regulation mechanism of UrTCP in the TIAs biosynthesis pathway is yet unknown. In this study, twenty-six UrTCP genes were identified from the genome of U. rhynchophylla, and these genes were classified into three subgroups based on the phylogenetic analysis. UrTCPs from the same group or subgroup share comparable gene structures and conserved motifs. These 26 UrTCP genes were unevenly distributed throughout 22 chromosomes, and gene segmental duplication occurred. The interspecific co-linearity analysis suggested that UrTCP4 may have an important function in evolutionary process. The expression patterns analysis of UrTCP genes by RT-qPCR showed most UrTCP genes had the highest expression in leaves and stem hooks. The results of co-expression analysis and phylogenetic relationships screened UrTCP4 as the most likely participant in TIAs and its precursor synthesis. Furthermore, the subcellular localization of UrTCP4 indicated that it is located in nucleus. Dual luciferase assays revealed the UrTCP4 protein could activate or repress the transcription of UrLAMT and Ur7-DLH in the TIAs synthesis pathway. Finally, Yeast-one-hybrid assays demonstrated that the UrTCP4 protein can bind to the promoters of UrLAMT and Ur7-DLH. Thus, UrTCP4 may be involved in the regulation of the TIAs biosynthesis pathway. This research establishes a groundwork for elucidating the functions of UrTCP gene family in U. rhynchophylla, offering new insights into the regulation of TIAs.